Early and Long-term Consequences of Nutritional Stunting: From Childhood to Adulthood: Early and Long-term Consequences of Nutritional Stunting - De Sanctis, Vincenzo; Soliman, Ashraf; Alaaraj, Nada; Ahmed, Shayma; Alyafei, Fawziya; Hamed, Noor (Acta Biomedica Atenei Parmensis, 2021)
Summary. Linear growth failure (stunting) in childhood is the most prevalent form of undernutrition globally. The debate continues as to whether children who become stunted before age 24 months can catch up in growth and cognitive functions later in their lives. The potentially irreparable physical and neurocognitive damage that accompanies stunted growth is a major obstacle to human development. This review aims at evaluation and summarizing the published research covering the different aspects of stunting from childhood to adulthood.